Peran Kualitas Pelayanan, Emosional Marketing, dan Spiritual Marketing terhadap Loyalitas Customer pada Penerbit Tiga Serangkai Cabang Cirebon - Ma'mur Munajat; Dewi fatmasari; Alvien Septian Haerisma (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the influence of service quality, emotional marketing, and spiritual marketing on customer loyalty at Tiga Serangkai Publishing, Cirebon Branch. Customer loyalty is a crucial factor in maintaining business sustainability, particularly in the publishing industry, which faces intense competition and changes in consumer behavior. This research employs a quantitative approach using a survey method conducted among customers of Tiga Serangkai Publishing, Cirebon Branch. Data were collected through questionnaires and analyzed using multiple linear regression analysis. The results indicate that service quality, emotional marketing, and spiritual marketing have a positive and significant effect on customer loyalty, both partially and simultaneously. Among these variables, service quality has the most dominant influence on customer loyalty. These findings suggest that improving service quality, supported by emotional approaches and spiritual values, can strengthen long-term relationships between the company and its customers. This study is expected to serve as a reference for publishing management in formulating marketing strategies oriented toward customer loyalty.